COGNITIVE ENDOPHENOTYPES OF MODERN AND EXTINCT HOMININS ASSOCIATED WITH NTNG GENE PARALOGS - Prosselkov, Pavel; Hashimoto, Ryota; Polygalov, Denis; Ohi Kazutaka; Zhang, Qi; Mchugh, Thomas J; Takeda, Masatoshi; Itohara, Shigeyoshi (bioRxiv, 2016)
A pair of vertebrate-specific and brain-expressed pre-synaptic genes, NTNG1 and NTNG2, contributes to the Intellectual Quotient (IQ) test scores in a complementary manner. Single nucleotide polymorphisms (SNPs) of NTNG1 are associated with attenuated verbal comprehension (VC) or processing speed (PS) while NTNG2 SNPs affect working memory (WM) and perceptual organization (PO), forming cognitive endophenotypes in healthy and schizophrenia (SCZ)-affected human subjects. Regions of interest (ROIs), defined as 21 nucleotide (nu) long NTNG gene loci symmetrically embedding the IQ-affecting mutation alleles (VC/PS and WM/PO), underwent dramatic evolutionary changes from mice through primates to hominins, at the accelerated rates. Mutation alleles associated with the higher VC and WM IQ scores are found in the genomes of extinct hominins of Neolithic times, however, lower WM scores associated allele is also detectable in Mesolithic hunters genomes. Protein sequence of NTNG1 is 100% conserved among the primates, archaic and modern extinct hominins while NTNG2 underwent a recent selection sweep encoding a primate-specific S371A/V (~50,000 yrs BC), and a modern human (5,300 yrs BC) T346A substitutions. We show that a 500 mln yrs old genomic duplication of a synapse primordial gene provided a substrate for further synapse elaborations and its ultimate capacitive expansion of what evolved into a vertebrate cognitive superior complexity, intelligence.